2007
DOI: 10.1159/000107569
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of Sleep Complaints: Patients’ Subjective Responses

Abstract: Background: This study set out to evaluate whether patients’ expectations affected their responses to treatment of a sleep disorder. Methods: Fifty consecutive patients attending a sleep clinic for the first time and who had different diagnoses of sleep disorders were included in this study. The patients completed a set of 6 questionnaires on 7 occasions as they progressed through the process of a sleep clinic referral, assessment and treatment. Self-report questionnaires were used to assess their sleepiness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Given the need to develop new approaches to the treatment of residual and subclinical symptoms [34,35,36,37,38,39] and that cognitive deficits are present even in patients who have responded to antidepressant treatments [8], the ability to use a short, pertinent self-rating scale sensitive to change may facilitate the efficacy assessment of new interventions which specifically target these symptoms. Further studies will be needed to assess the validity and reliability of the CPFQ in other psychiatric and neuropsychiatric conditions associated with cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Given the need to develop new approaches to the treatment of residual and subclinical symptoms [34,35,36,37,38,39] and that cognitive deficits are present even in patients who have responded to antidepressant treatments [8], the ability to use a short, pertinent self-rating scale sensitive to change may facilitate the efficacy assessment of new interventions which specifically target these symptoms. Further studies will be needed to assess the validity and reliability of the CPFQ in other psychiatric and neuropsychiatric conditions associated with cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Sleepiness, fatigue, and sleep deprivation negatively affect functioning, resulting in decreased productivity, 17,18 increased errors and workplace accidents, 19,20 traffic collisions, 21,22 and deterioration of relationships, 23 and may trigger a general decline in health and well-being. 24,25 Fatigue, often reported by shift workers, is significantly ( p ¼ 0.01) correlated with poorer sleep quality, 26 and based on a large epidemiological study, females are twice as likely to report workplace fatigue (OR 2.3, 95% CI 1.9-2.8). 9 The impact of shift schedule on sleep also deserves consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Initial testing in a group of 50 patients repeatedly assessed (on six occasions) with these two scales over a 6-month period showed that they were easy to use, required little instruction, and showed variation in scores across individuals, time, and treatment circumstances [27].…”
Section: Scale Developmentmentioning
confidence: 99%